2004
DOI: 10.1111/j.1600-0463.2004.apm11204-0504.x
|View full text |Cite
|
Sign up to set email alerts
|

Macroscopic oropharyngeal signs indicating impaired defensive function of palatine tonsils in adults suffering from recurrent tonsillitis

Abstract: The present study explored in adults suffering from recurrent tonsillitis the association between macroscopic oropharyngeal signs of recurrent inflammation, immunomorphology of palatine tonsils (counts of neutrophils by CD4 and macrophages by CD68 monoclonal antibodies in tonsillar microcompartments) and the occurrence of post-tonsillectomy bacteremia. The study involved 50 adults (31 females and 19 males) with recurrent tonsillitis. According to predominance of either inflammatory changes or evidence of scler… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 32 publications
1
7
0
Order By: Relevance
“…Our study suggested that this negative result of blood culture might be due to administration of antibiotic before collecting of blood from patients who were no in febrile period in which the bacteria were shedding from blood. The results of this study that revealed 59.7% GABHS diagnosed by PCR and 20.8% of these microorganisms detected by serogrouping method and this was agreed with findings of other study, Kasenomm, P. et al (2004), who found that 42% GABHS positive by PCR and 30% positive by culture. The present study indicated highly specificity and sensitivity of PCR than culture technique and PCR is the best choice for diagnosis of infection with beta-hemolytic streptococci and these finding was in contrast with findings from several studies in many countries which indicated the specificity and sensitivity of culture technique in comparing with PCR (20-21).…”
Section: Discussionsupporting
confidence: 92%
“…Our study suggested that this negative result of blood culture might be due to administration of antibiotic before collecting of blood from patients who were no in febrile period in which the bacteria were shedding from blood. The results of this study that revealed 59.7% GABHS diagnosed by PCR and 20.8% of these microorganisms detected by serogrouping method and this was agreed with findings of other study, Kasenomm, P. et al (2004), who found that 42% GABHS positive by PCR and 30% positive by culture. The present study indicated highly specificity and sensitivity of PCR than culture technique and PCR is the best choice for diagnosis of infection with beta-hemolytic streptococci and these finding was in contrast with findings from several studies in many countries which indicated the specificity and sensitivity of culture technique in comparing with PCR (20-21).…”
Section: Discussionsupporting
confidence: 92%
“…As the parenchymal fibrosis leads to lowered count of neutrophils in tonsillar tissue, increasing the risk for spread of bacteria into the bloodstream and infection generalization [9], removal of such functionally compromised tonsils could be justified. However, considering the sclerotic signs as the only indicator for TE, particularly in adults with lower rate of tonsillitis episodes, may lead to an overestimation of the need for surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The sclerotic process in tonsils was further evidenced by increased collagen content. It revealed that sclerotic type tonsils had remarkably lower count of neutrophils in its tissue, which increased the risk for bacteraemia during tonsillectomy [9]. Thus, extensive tissue fibrosis seemed to be a critical point in the RT pathogenesis where the defensive function of tonsils becomes impaired.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, macroscopic oropharyngeal signs were evaluated and the index of tonsillitis (IT) was calculated as described in our previous studies ( 12 , 13 ). Macroscopic oropharyngeal signs were evaluated on tonsill in the opposite side of PTA and they were as follows: tonsillar sclerosis, obstruction of the tonsillar crypts, scar tissue on tonsils, cryptic debris, and lymphatic tissue aggregates.…”
Section: Methodsmentioning
confidence: 99%